The boundedness of multilinear commutators on locally compact Vilenkin groups - Canqin Tang (Journal of Function Spaces and Applications)
Let G be a locally compact Vilenkin group. In this paper, the authors investigate the boundedness of multilinear commutators of fractional integral operator on Lebesgue spaces on G. Furthermore, the boundedness on Hardy spaces are also obtained in this paper.